Perlindungan Hukum Terhadap Protokol Notaris Dari Notaris Yang Meninggal Dunia Di Kabupaten Temanggung - Angie Athalia Kusuma (Officium Notarium, 2021)
This study discusses first, the legal protection of the Notary Protocol for a Notary who passed away in Temanggung Regency; and second, the role of the Notary Regional Supervisory Council (MPD) in Temanggung Regency in resolving the Notary Protocol issue. The type of research used is empirical with a sociological juridical approach and qualitative data analysis. The result of this study conclude, first, that the legal protection of the Notary Protocol in Temanggung Regency has not been fully implemented in accordance with Article 16 letter b of the UUJN. In the first case there is still a Notary Protocol that has been lost due to the actions of uncooperative heirs and in the second case the Notary Protocol has landed on the right hands because the Notary who gave the Notary Protocol had realized that they would soon retire and acknowledged the importance of the Notary Protocol as state archives which must be protected and delegated to the right person. The second result showed that Temanggung district MPD has played an active role in providing guidance and supervision to the Notary but the recipient of the Notary Protocol cannot cooperate well hence the role of MPD is not optimalized.Keywords: Legal protection; notary protocol; notary supervisory councilAbstrakPenelitian ini membahas tentang pertama, perlindungan hukum terhadap Protokol Notaris dari Notaris yang meninggal dunia di Kabupaten Temanggung; dan kedua, peran Majelis Pengawas Daerah (MPD) Notaris di Kabupaten Temanggung menyelesaikan masalah Protokol Notaris. Jenis penelitian yang digunakan adalah empiris dengan pendekatan yuridis sosiologis serta analisa data secara kualitatif. Hasil penelitian ini menyimpulkan, pertama, perlindungan hukum terhadap protokol Notaris di Kabupaten Temanggung belum sepenuhnya berjalan sesuai dengan Pasal 16 huruf b UUJN. Pada kasus pertama masih ada protokol Notaris yang hilang jejaknya dikarenakan ulah ahli waris yang tidak kooperatif dan pada kasus kedua protokol Notaris sampai ditangan yang tepat karena Notaris pemberi protokol Notaris menyadari bahwa dirinya akan pensiun dan Notaris pemberi protokol Notaris menyadari pentingnya protokol Notaris sebagai arsip milik Negara yang harus dilindungi dan dilimpahkan kepada orang yang tepat. Kedua, MPD abupaten Temanggung sudah berperan aktif dalam melakukan pembinaan dan pengawasan kepada Notaris tetapi Notaris penerima protokol Notaris tidak dapat bekerjasama sehingga peran MPD menjadi tidak optimal.Kata Kunci: Majelis pengawas notaris; perlindungan hukum; protokol notaris